2017
DOI: 10.21273/jashs03830-16
|View full text |Cite
|
Sign up to set email alerts
|

Light Intensity and Light Quality from Sole-source Light-emitting Diodes Impact Phytochemical Concentrations within Brassica Microgreens

Abstract: Multilayer vertical production systems using sole-source (SS) light-emitting diodes (LEDs) can be an alternative to more traditional methods of microgreens production. One significant benefit of using LEDs is the ability to select light qualities that have beneficial impacts on plant morphology and the synthesis of health-promoting phytochemicals. Therefore, the objective of this study was to quantify the impacts of SS LEDs of different light qualities and intensities on the phytochemical content of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 38 publications
3
64
0
2
Order By: Relevance
“…Changes in polyphenol and anthocyanin content were observed in many of the above-referenced reports and in others (e.g. Craver et al 2017). Even levels of secondary metabolites like 'essential oils' can be influenced by light inputs (Sabzalian et al 2014).…”
Section: Nutrients and Neutraceuticalsmentioning
confidence: 82%
See 1 more Smart Citation
“…Changes in polyphenol and anthocyanin content were observed in many of the above-referenced reports and in others (e.g. Craver et al 2017). Even levels of secondary metabolites like 'essential oils' can be influenced by light inputs (Sabzalian et al 2014).…”
Section: Nutrients and Neutraceuticalsmentioning
confidence: 82%
“…Craver et al . ). Even levels of secondary metabolites like ‘essential oils’ can be influenced by light inputs (Sabzalian et al .…”
Section: Nutrients and Neutraceuticalsmentioning
confidence: 97%
“…Most research on microgreens has taken place in the last 7 years by a limited but growing number of international research groups (Brazaitytė et al., ; Craver, Gerovac, Lopez, & Kopsell, ; Kyriacou et al., ; Riggio, Wang, Kniel, & Gibson, ; Xiao et al., ). Each group has focused on a narrow subset of microgreens and their issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies revealed that variation in microgreens' content of bioactive compounds is based on several pre-harvest factors such as genetic material (i.e., species), conditions of cultivation and light parameters (i.e., spectral quality and intensity), additional variables have also been implicated in shaping microgreens' nutritive and phytochemical composition, including nutrition/biofortification and choice of growth medium [4,10,[12][13][14][15][16][17][18][19][20][21]. Notwithstanding the short crop cycle, special attention must be placed on the selection of growth media for microgreens, which represents one of the most important factors in the production process influencing microgreens quality [22].…”
Section: Introductionmentioning
confidence: 99%